Islamic Ethics-by-Design for Artificial Intelligence: A Conceptual Framework for Digital Ethics in Islamic Education. - Rizqia, Anggun Pamela; Mustofa, Triono Ali (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
This article reviews the challenges of digital ethics in the era of the artificial intelligence (AI) revolution from an Islamic perspective, especially in the context of Islamic Religious Education (PAI), da'wah, and the moral crisis of Generation Z who are exposed to digital globalization, with the aim of designing a framework for the development of AI based on sharia maqasid for the benefit of the ummah. The qualitative research methodology of library research analyzes journals, the Qur'an, hadith, and related literature through secondary data collection, critical literature studies, and content synthesis for the identification of ethical principles; findings show that AI has the potential to transform personal education, efficient digital zakat, adaptive da'wah chatbots but risk deepfake hoaxes, privacy violations, algorithmic bias, and hegemony of thought if not based on religious values such as responsibility for information (Q.S Al-Isra':36), respect for privacy (Q.S Al-Hujurat:12), and use for the social good; Its originality lies in Islamic ethics-by-design that integrates sharia regulations, PAI digital literacy via moral knowing-habituation-culturalization, and the Sharia AI Ethics Council which is relevant for Indonesian educators to form a pious generation in the midst of technological disruption.